Xylene gas sensor based on Co3O4 and In2O3 heterojunction as well as preparation process and application of xylene gas sensor
By using Co3O4 and In2O3 heterojunction composite nanomaterials in the gas-sensitive sensor, the existing n-type metal oxide semiconductor gas-sensitive sensors are solved, and a xylene gas sensor with high selectivity, sensitivity and stability is realized, reducing the detection lower limit and optimizing the working temperature.
Patent Information
- Application Number
- CN202510024800.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-18
AI Technical Summary
The existing n-type metal oxide semiconductor gas-sensitive sensors have poor selectivity when detecting volatile organic compounds (VOCs), especially at low temperatures, and their performance is not as good as p-type oxides, and their response recovery time and catalytic activity are insufficient.
A gas sensor based on Co3O4 and In2O3 heterojunction is used to prepare cobalt tetraoxide and indium trioxide materials by hydrothermal method, and composite nanomaterials are formed through grinding, ultrasonic, magnetic stirring, etc., and coated on alumina ceramic tube to achieve gas sensitive detection.
The selectivity, sensitivity and stability of the xylene gas sensor is significantly improved, the lower detection limit is reduced, and there is still a significant response at the xylene concentration of 0.1ppm, and the operating temperature is slightly reduced.
Smart Images

Figure CN119846030A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic components and relates to a xylene gas sensor based on a Co3O4 and In2O3 heterojunction, a preparation process and an application thereof. Background Art
[0002] With the rapid development of industrialization, the emission of various toxic and harmful gases in production and life has posed a great threat to people's health. Volatile organic compounds (VOC) are a common category of harmful gases. Xylene belongs to volatile organic compounds (VOC). Light aromatics are one of the light aromatics. They are widely used and are the basic organic chemical raw materials for the petrochemical industry. It is worth noting that xylene can seriously damage the human nervous system. In addition, xylene is listed in the list of Class III carcinogens. In order to avoid the pollution of the atmospheric environment and the harm to people's health caused by xylene, real-time monitoring of xylene in industrial production is particularly necessary. Therefore, a gas sensor that can detect the concentration of xylene in the atmosphere is very necessary in production and life.
[0003] At present, among the many types of gas sensors, the research and preparation technology of gas sensors based on metal oxides is the most mature, and it is widely used because of its reliable quality and low price. Generally, the detection of target gas is achieved based on the change of carrier concentration in the material. According to the different types of carriers, metal oxide semiconductor sensors can be divided into n-type and p-type. Due to the different carriers, there are certain differences in the response characteristics of p-type and n-type semiconductor materials. For materials with the same configuration, the response value of n-type semiconductors is often better than that of p-type semiconductors. However, compared with p-type oxides, n-type oxides have poor selectivity for volatile organic compounds (VOCs), especially at low temperatures. The working performance is not as good as that of p-type oxides. Moreover, the response recovery time and catalytic activity are also somewhat different from those of p-type oxides. Based on Co3O4, a typical p-type metal oxide semiconductor, it is used in the research of gas sensors due to its advantages such as non-toxicity, high conductivity and corrosion resistance. In order to further improve the performance of gas sensors, researchers have achieved this by regulating the morphology of the material, and prepared hollow nano-spherical Co3O4 materials by hydrothermal method. The hollow shell structure has a small density while maintaining a huge specific surface area. A larger specific surface area means that the material surface can carry more active sites. The redox reaction on the surface of the material generally takes place on the active sites. A larger specific surface area can usually improve the gas sensing performance of the material very intuitively. At present, in order to further improve the gas sensing properties of gas sensors, a heterojunction structure of a pn mixed oxide is formed by doping. TANG Wei, WANG Jing and others proposed in "Enhanced Gas Sensing Mechanisms of Metal Oxide Heterojunction Gas Sensors" that due to the different Fermi levels of the two, electrons and holes are transferred, a space charge layer is formed at the interface, the energy band is bent, and a potential barrier is generated. This phenomenon is called "Fermi level-mediated charge transfer", which greatly narrows the electron transport channel. According to the oxygen adsorption model, when oxygen in the air is adsorbed on the outer surface of the pn heterostructure, the electron transport channel is suppressed. If two materials with large Fermi level differences can be found as gas sensing materials, the charge conduction channel can be further narrowed, thereby improving the gas sensing performance. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the existing n-type metal oxide semiconductor gas sensor, provide a xylene gas sensor with good selectivity, high sensitivity, good stability and low detection limit and a detection method thereof, and provide the possibility of realizing portable and miniaturized gas sensing equipment. It is known that the band gap width of Co3O4 is 1.5-2.2eV, so In2O3 with a band gap width of 6.0eV can be considered as an excellent material for compounding with Co3O4 to achieve sensitivity enhancement modification.
[0005] The technical solution of the present invention:
[0006] A xylene gas sensor based on a Co3O4 and In2O3 heterojunction mainly consists of a gas-sensitive material and an alumina ceramic tube, wherein the gas-sensitive material is coated on the alumina ceramic tube with a coating thickness of 40 μm to 80 μm; the gas-sensitive material is a cobalt tetroxide and indium trioxide heterojunction composite nanomaterial.
[0007] The alumina ceramic tube is an alumina hollow tube with a columnar body and a pure gold electrode, with a tube length of 4 mm, an outer diameter of 1.2 mm, and an inner diameter of 0.9 mm.
[0008] The cobalt tetroxide and indium trioxide heterojunction composite nanomaterial is firstly prepared by a hydrothermal method to obtain cobalt tetroxide and indium trioxide materials respectively, and then physically compounded in a certain proportion by grinding, ultrasound, magnetic stirring and the like.
[0009] The working environment temperature of the xylene gas sensor is 240° C. to 330° C., and the material is integrated with silicon-based microelectronics.
[0010] A preparation process of a xylene gas sensor based on a Co3O4 and In2O3 heterojunction comprises the following steps:
[0011] (1) Co(NO3)2·6H2O and deionized water were added to methanol to control the Co 2+ The concentration in methanol is 0.10-0.12 mol / L, the volume ratio of methanol to deionized water is 11-27.5, and magnetic stirring is performed until the mixture is completely dissolved to obtain a mixed solution;
[0012] (2) adding sodium dodecylbenzene sulfonate to the mixed solution obtained in step (1), stirring with a magnetic force until a uniform suspension is formed, controlling the concentration of SDBS to be 0.025 to 0.030 mol / L, and then performing ultrasonic treatment for 30 min to obtain a suspension;
[0013] (3) transferring the suspension obtained in step (2) to a hydrothermal reaction kettle lined with polytetrafluoroethylene, performing a hydrothermal reaction at 180° C. to 200° C. for 4 h, separating the product after the hydrothermal reaction into solid and liquid using a centrifuge, washing the obtained solid product with deionized water and anhydrous ethanol in turn for multiple times, placing the obtained solid product in a vacuum drying oven, and drying it at 60° C. to 90° C. for more than 2 h to obtain a material with a cobalt oxide hollow nanosphere morphology;
[0014] (4) In(NO3)3·xH2O was dissolved in a mixed solution of 25% NH3·H2O and ethanol, and the volume ratio of 25% NH3·H2O and ethanol was controlled to be 1:5. 3+ The concentration was maintained between 0.04 and 0.06 mol / L. The mixture was stirred magnetically for more than 3 hours to obtain a clear and transparent mixture solution.
[0015] (5) transferring the mixture solution obtained in step (4) to a hydrothermal reactor lined with polytetrafluoroethylene, performing a hydrothermal reaction at a temperature of 100° C. to 120° C. for 24 hours, separating the product after the hydrothermal reaction into solid and liquid using a centrifuge, and washing the obtained solid product with deionized water and anhydrous ethanol in turn for multiple times, placing the obtained solid product in a drying oven, and drying it at 60° C. to 90° C. for 20 hours to 24 hours to obtain a precursor, and then heating the obtained precursor at 500° C. in a muffle furnace for 2 hours to obtain indium trioxide nanoparticles;
[0016] (6) The cobalt oxide obtained in step (3) and the indium oxide obtained in step (5) are mixed and ground into powder in a certain ratio, and the molar ratio of Co3O4 to In2O3 is controlled between 2:1 and 999:1. The ground cobalt oxide and indium oxide composite powder is then dispersed in deionized water, ultrasonically treated to form a dispersion of 8 mg / mL to 10 mg / mL, and then the dispersion is coated on the surface of the alumina ceramic tube, placed in a vacuum drying oven at 60°C for 15 to 30 minutes, and naturally cooled to room temperature to obtain a Co3O4 / In2O3 nanocomposite gas sensor.
[0017] In step (2), the ultrasonic power is 240W to 260W.
[0018] The working temperature of the gas sensor prepared based on Co3O4 / In2O3 nanocomposite materials is 240℃~330℃, realizing the integration of the material with silicon-based microelectronics.
[0019] Working principle of the present invention: The xylene gas sensor of the present invention is a resistive semiconductor gas sensor, which mainly utilizes the fact that when the semiconductor contacts the gas to be measured, the redox reaction occurring on its surface causes the change in carrier concentration, thereby causing the change in the resistance of the semiconductor, and thereby reflects the type and concentration of the gas to be measured. The xylene gas sensor of the present invention uses cobalt tetroxide as the main material, and cobalt tetroxide is a p-type metal oxide semiconductor, and the carriers are holes. Therefore, the gas molecules to be measured adsorbed on the surface of the semiconductor react with the oxygen anions (O2 - , O - , O 2-) undergoes an oxidation-reduction reaction, which changes the carrier concentration in the semiconductor, thereby causing a change in the semiconductor's electrical conductivity. The real-time monitoring signal of the sensor is the change in the sensor's resistance value.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention adopts a hydrothermal method to obtain a novel heterojunction composite nanomaterial. The raw materials are easy to obtain, low in price, and the heterojunction preparation process is simple. It is a semiconductor heterojunction preparation solution with small equipment investment and simple process flow.
[0022] (2) The composite material of the present invention has In2O3 nanoparticles evenly distributed on the surface of the hollow nanosphere Co3O4, and has a large surface area-volume ratio structure. At the same time, cobalt tetroxide and indium trioxide produce a heterojunction, which can guide electrons to accumulate on the surface material and enhance the gas-sensitive selectivity of the material. The electron migration between cobalt tetroxide and indium trioxide helps to promote additional oxygen adsorption on the surface of the material, thereby improving the gas-sensitive performance.
[0023] (3) The present invention greatly reduces the gas detection limit of the sensor, and still has an obvious response when the xylene concentration is 0.1ppm, slightly reducing the operating temperature. At the same time, the extremely small detection limit makes it possible to detect trace amounts of harmful gases. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The XRD spectra are obtained to characterize the Co3O4 / In2O3 nanocomposite materials obtained in Example 1, Example 2, and the Co3O4 / In2O3 nanocomposite materials obtained by using the same process as the two examples but with different doping ratios, as well as the pure Co3O4 material obtained in Example 3.
[0025] Figure 2 This is a SEM scanning electron microscope microscopic morphology image of the Co3O4 / In2O3 nanocomposite material of the present invention.
[0026] Figure 3 TEM transmission electron microscope images of the Co3O4 / In2O3 nanocomposite material of the present invention, wherein (a) is the TEM transmission electron microscope microscopic morphology image of the Co3O4 / In2O3 nanocomposite material of the present invention; (b) is the heterojunction structure of Co3O4-In2O3; (c) is the lattice fringes of Co3O4 and the corresponding crystal plane data; (d) is the lattice fringes of In2O3 and the corresponding crystal plane data.
[0027] Figure 4 This is a comparison diagram of the responses of the Co3O4 / In2O3 nanocomposite gas sensor of the present invention to several common volatile interfering gases and xylene.
[0028] Figure 5This is the response curve of Co3O4 / In2O3 nanocomposite gas sensor under different xylene concentrations.
[0029] Figure 6 This is the response curve of Co3O4 / In2O3 nanocomposite gas sensor to 5 ppm xylene at different composite ratios.
[0030] Figure 7 The figure is a comparison of the gas sensing properties of the pure Co3O4 hollow nanosphere material prepared in Example 3 and the Co3O4 nanocube material prepared in Example 4 under the conditions of 10 ppm xylene and 270°C. Compared with other morphologies, the Co3O4 hollow nanospheres prepared by the preparation method of the present invention have better performance.
[0031] Figure 8 The gas sensitive response of the Co3O4 / ZnO nanocomposite gas sensor with different ratios to 5 ppm xylene at 20% to 30% RH and different temperatures was prepared by the method in Example 5. It can be seen that compared with the Co3O4 / In2O3 nanocomposite used in the present invention, the responsiveness of the Co3O4 / ZnO nanocomposite gas sensor is significantly lower.
[0032] Fig. 9 The gas-sensitive response of the Co3O4 / GO nanocomposite gas sensor prepared in Example 6 is very good, but the recovery time of the device is obviously too long and the practical application value is very low. DETAILED DESCRIPTION
[0033] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0034] Example 1
[0035] (1) Dissolve 0.698 g of cobalt nitrate hexahydrate (Co(NO3)3·6H2O) and 0.8 mL of deionized water (DI Water) in 22 mL of methanol.
[0036] (2) 1.986 g of sodium dodecylbenzene sulfonate (SDBS) was added to the mixed solution obtained in step (1), and magnetic stirring was performed until the drug formed a uniform suspension, followed by ultrasonic treatment for 30 min at an ultrasonic power of 240 W.
[0037] (3) The suspension obtained in step (2) was transferred to a 50 mL hydrothermal reactor lined with polytetrafluoroethylene, and the hydrothermal reaction was carried out at a temperature of 200° C. for 4 h. The product after the hydrothermal reaction was separated into solid and liquid by a centrifuge, and the solid product was washed with deionized water and anhydrous ethanol in turn. The solid product was placed in a vacuum drying oven and dried at 90° C. for 24 h to obtain cobalt oxide hollow nanosphere material.
[0038] (4) 0.451 g of hydrated indium nitrate (In(NO3)3·xH2O) was dissolved in a mixed solution of 6 mL of 25% NH3·H2O and 30 mL of ethanol, and magnetic stirring was performed for 3 h until the mixture solution became clear.
[0039] (5) The solution obtained in step (4) is transferred to a 50 mL hydrothermal reactor lined with polytetrafluoroethylene, and the hydrothermal reaction is carried out at a temperature of 100° C. for 24 hours. The product after the hydrothermal reaction is separated into solid and liquid by a centrifuge, and the solid product is washed multiple times with deionized water and anhydrous ethanol in turn. The solid product is placed in a drying oven and dried at 90° C. for 24 hours to obtain a precursor. The obtained precursor is then heated in a muffle furnace at 500° C. for 2 hours to obtain indium trioxide nanoparticles.
[0040] (6) The cobalt tetroxide obtained in step (3) and the indium trioxide obtained in step (5) are mixed and ground into powder in a molar ratio of 997:3, and the ground cobalt tetroxide and indium trioxide composite material powders are dispersed in deionized water, ultrasonically treated to form a 10 mg / mL dispersion, and then the dispersion is coated on the surface of the alumina ceramic tube (the ceramic tube is used as an electrode with a gold ring spacing of 1.15 mm and a gold ring width of 0.5 mm. A heating platinum wire passes through the middle of the tube with a resistance of about 30-33Ω) and placed in a drying oven at 60°C for 30 min, and naturally cooled to room temperature to obtain a Co3O4 / In2O3 nanocomposite gas sensor.
[0041] Example 2
[0042] (1) Dissolve 0.698 g of cobalt nitrate hexahydrate (Co(NO3)3·6H2O) and 0.8 mL of deionized water (DI Water) in 22 mL of methanol.
[0043] (2) 1.986 g of sodium dodecylbenzene sulfonate (SDBS) was added to the mixed solution obtained in step (1), and magnetic stirring was performed until the drug formed a uniform suspension, followed by ultrasonic treatment for 30 min at an ultrasonic power of 240 W.
[0044] (3) The suspension obtained in step (2) was transferred to a 50 mL hydrothermal reactor lined with polytetrafluoroethylene, and the hydrothermal reaction was carried out at a temperature of 200° C. for 4 h. The product after the hydrothermal reaction was separated into solid and liquid by a centrifuge, and the solid product was washed with deionized water and anhydrous ethanol in turn. The solid product was placed in a vacuum drying oven and dried at 90° C. for 24 h to obtain cobalt oxide hollow nanosphere material.
[0045] (4) 0.451 g of hydrated indium nitrate (In(NO3)3·xH2O) was dissolved in a mixed solution of 6 mL of 25% NH3·H2O and 30 mL of ethanol, and magnetic stirring was performed for 3 h until the mixture solution became clear.
[0046] (5) The solution obtained in step (4) is transferred to a 50 mL hydrothermal reactor lined with polytetrafluoroethylene, and the hydrothermal reaction is carried out at a temperature of 100° C. for 24 hours. The product after the hydrothermal reaction is separated into solid and liquid by a centrifuge, and the solid product is washed multiple times with deionized water and anhydrous ethanol in turn. The solid product is placed in a drying oven and dried at 90° C. for 24 hours to obtain a precursor. The obtained precursor is then heated in a muffle furnace at 500° C. for 2 hours to obtain indium trioxide nanoparticles.
[0047] (6) The cobalt tetroxide obtained in step (3) and the indium trioxide obtained in step (5) are mixed and ground into powder in a molar ratio of 97:3, and the ground cobalt tetroxide and indium trioxide composite material powders are dispersed in deionized water, ultrasonically treated to form a 10 mg / mL dispersion, and then the dispersion is coated on the surface of the alumina ceramic tube (the ceramic tube is used as an electrode with a gold ring spacing of 1.15 mm and a gold ring width of 0.5 mm. A heating platinum wire passes through the middle of the tube with a resistance of about 30-33 Ω) and placed in a drying oven at 60° C. for 30 min, and naturally cooled to room temperature to obtain a Co3O4 / In2O3 nanocomposite gas sensor.
[0048] Example 3
[0049] (1) Dissolve 0.698 g of cobalt nitrate hexahydrate (Co(NO3)3·6H2O) and 0.8 mL of deionized water (DI Water) in 22 mL of methanol.
[0050] (2) 1.986 g of sodium dodecylbenzene sulfonate (SDBS) was added to the mixed solution obtained in step (1), and magnetic stirring was performed until the drug formed a uniform suspension, followed by ultrasonic treatment for 30 min at an ultrasonic power of 240 W.
[0051] (3) The suspension obtained in step (2) was transferred to a 50 mL hydrothermal reactor lined with polytetrafluoroethylene, and the hydrothermal reaction was carried out at a temperature of 200° C. for 4 h. The product after the hydrothermal reaction was separated into solid and liquid by a centrifuge, and the solid product was washed 5 times with deionized water and anhydrous ethanol respectively. The solid product was placed in a vacuum drying oven and dried at 90° C. for 24 h to obtain cobalt oxide hollow nanosphere material.
[0052] Example 4
[0053] (1) Dissolve 11.64 g of cobalt nitrate hexahydrate (Co(NO3)3·6H2O) in 40 mL of deionized water (DI Water), add 3.75 g of NaOH, and stir magnetically at room temperature for 10 min to obtain a purple solution.
[0054] (2) The solution obtained in step (1) was transferred to a 50 mL hydrothermal reactor lined with polytetrafluoroethylene, and the hydrothermal reaction was carried out at a temperature of 180° C. for 5 h. The product after the hydrothermal reaction was separated into solid and liquid by a centrifuge, and the solid product was washed 5 times with deionized water and anhydrous ethanol respectively. The solid product was placed in a drying oven and dried at 60° C. for 24 h to obtain a precursor.
[0055] (3) The precursor obtained in step (2) was transferred to a muffle furnace and calcined at 500° C. for 4 h at a heating rate of 5° C. / min to finally obtain Co3O4 nanocube black powder.
[0056] Example 5
[0057] (1) Dissolve 0.698 g of cobalt nitrate hexahydrate (Co(NO3)3·6H2O) and 0.8 mL of deionized water (DI Water) in 22 mL of methanol.
[0058] (2) 1.986 g of sodium dodecylbenzene sulfonate (SDBS) was added to the mixed solution obtained in step (1), and magnetic stirring was performed until the drug formed a uniform suspension, followed by ultrasonic treatment for 30 min at an ultrasonic power of 240 W.
[0059] (3) The suspension obtained in step (2) was transferred to a 50 mL hydrothermal reactor lined with polytetrafluoroethylene, and the hydrothermal reaction was carried out at a temperature of 200° C. for 4 h. The product after the hydrothermal reaction was separated into solid and liquid by a centrifuge, and the solid product was washed 5 times with deionized water and anhydrous ethanol respectively. The solid product was placed in a vacuum drying oven and dried at 90° C. for 24 h to obtain cobalt oxide hollow nanosphere material.
[0060] (4) Dissolve 1.000 g of zinc acetate ((CH3COO)2Zn) and 3.000 g of urea in 40 mL of deionized water (DI Water), and ultrasonicate for 30 min at room temperature with an ultrasonic power of 240 W to obtain a mixed solution.
[0061] (5) The mixed solution obtained in step (4) was transferred to a 50 mL hydrothermal reactor lined with polytetrafluoroethylene, and the hydrothermal reaction was carried out at 100° C. for 6 h. The product after the hydrothermal reaction was separated into solid and liquid by a centrifuge, and the solid product was washed 5 times with deionized water and anhydrous ethanol respectively, and dried in a drying oven at 60° C. for 24 h to obtain a solid powder.
[0062] (6) The product prepared in step (5) was placed in a muffle furnace and calcined at 300° C. for 2 h at a heating rate of 5° C. / min to obtain a ZnO nanosheet material.
[0063] (7) The cobalt oxide obtained in step (3) and the zinc oxide obtained in step (6) are mixed so that the molar ratio of ZnO is 3%, and the mixture is ground for 30 minutes. The ground cobalt oxide and zinc oxide composite powder is dispersed in deionized water, and ultrasonically treated to form a 10 mg / mL dispersion. The dispersion is then applied to the surface of the alumina ceramic tube (the spacing between the gold rings of the ceramic tube as an electrode is 1.15 mm, and the width of the gold ring is 0.5 mm. A heating platinum wire passes through the middle of the tube, and the resistance is about 30-33Ω). The mixture is placed in a drying oven at 60°C for 30 minutes and naturally cooled to room temperature to obtain a Co3O4 / ZnO nanocomposite gas sensor.
[0064] Example 6
[0065] (1) 3.5 mg of graphene oxide was added to 35 mL of deionized water (DI Water) and ultrasonically mixed and stirred at room temperature for 30 min with an ultrasonic power of 240 W.
[0066] (2) 0.051 g of cobalt nitrate hexahydrate (Co(NO3)3·6H2O) and 0.074 g of urea were added to the mixed solution obtained in step (1), and magnetic stirring was performed until the mixture was uniform.
[0067] (3) The liquid obtained in step (2) was transferred to a 50 mL hydrothermal reactor lined with polytetrafluoroethylene, and the hydrothermal reaction was carried out at 80° C. for 10 h. The product after the hydrothermal reaction was separated into solid and liquid by a centrifuge, and the solid product was washed with deionized water and anhydrous ethanol in turn. The solid product was placed in a vacuum drying oven and dried at 90° C. for 24 h to obtain a precursor.
[0068] (4) The precursor obtained in step (3) is placed in a N2 atmosphere tubular furnace and calcined at 500°C for 2 hours at a heating rate of 5°C / min. The resulting powder is a graded porous cobalt oxide nanosphere / graphene composite material.
[0069] The results are analyzed as follows: Figure 1 As shown, the XRD spectrum of the Co3O4 / In2O3 heterojunction structure sensitive material is compared with the XRD spectrum of the pure Co3O4 nanostructure sensitive material. The characteristic peaks of Co3O4 and In2O3 are consistent, which proves that the Co3O4 / In2O3 heterojunction structure sensitive material is composed of Co3O4 and In2O3.
[0070] like Figure 2As shown, the SEM image of the Co3O4 / In2O3 heterojunction structure shows that the surface of the nanosphere shell is dotted with nanoparticles.
[0071] like Figure 3 (a) shows the SEM image of the Co3O4 / In2O3 heterojunction structure, which shows that the surface of the nanosphere is dotted with nanoparticles. Figure 2 The morphology shown is uniform. High-resolution TEM images show lattice spacings of 0.2437 nm and 0.1788 nm wide, which are consistent with the (3 1 1) crystal plane of Co3O4 and the (4 4 0) crystal plane of In2O3, respectively.
[0072] like Figure 4 As shown, under the optimal working temperature conditions, the Co3O4 / In2O3 heterojunction structure sensitive material has good selectivity for xylene and its sensitivity is significantly higher than other common volatile organic compounds.
[0073] like Figure 5 As shown in the figure, the Co3O4 / In2O3 gas sensor exhibits excellent response and recovery characteristics to xylene at different concentrations. Moreover, the detection limit is low, and there is still an obvious response when the xylene concentration is 0.1ppm.
[0074] like Figure 6 As shown in the figure, the gas sensing properties of the gas sensor are significantly different when the composite ratio of Co3O4 / In2O3 heterojunction structure sensitive materials is different. When the molar ratio of In2O3 is 0.3%, the gas sensing properties of the Co3O4 / In2O3 heterojunction structure sensitive material reach the best.
[0075] like Figure 7 As shown, compared with the Co3O4 nanocubes obtained in Example 4, the Co3O4 hollow nanospheres prepared by the preparation method of the present invention have better performance. When the response time is roughly the same, it has higher sensitivity and shorter recovery time.
[0076] like Figure 8 As shown, compared with the Co3O4 / In2O3 nanocomposite material used in the present invention, the response of the Co3O4 / ZnO nanocomposite material gas sensor obtained in Example 5 is obviously lower.
[0077] like Fig. 9 As shown, the Co3O4 / GO nanocomposite gas sensor obtained in Example 6 has good sensitivity, but its recovery time is obviously too long and its practical application value is very low.
[0078] In general, the present invention starts from the microscopic morphology of the material, the selection of the composite material, and the doping ratio of the composite material, and gradually improves the various gas-sensitive properties of the gas-sensitive material to xylene. At the microscopic morphology level, the hollow nanospheres are uniform in size, low in density, and large in specific surface area, which can increase the effective area, improve the catalytic and adsorption properties of the material, and provide abundant active sites for redox reactions. These characteristics are very helpful for improving the performance of gas-sensitive elements. Therefore, selecting Co3O4 materials with hollow nanosphere morphology is the first step to improve gas-sensitive performance.
[0079] In the selection of composite materials to form heterojunction structures, according to the "Fermi level mediated charge transfer" theory proposed by TANG Wei, WANG Jing and others in "Enhanced Gas Sensing Mechanisms of Metal Oxide Heterojunction Gas Sensors", if two materials with large Fermi level differences can be found as gas-sensitive materials, the charge conduction channel can be further narrowed, thereby improving the gas-sensitive performance. Considering that Co3O4 is a p-type metal oxide semiconductor, the selection of an n-type metal oxide semiconductor will make the heterojunction effect stronger. When Co3O4 / In2O3 is exposed to air, O2 is adsorbed on the surface of the material and forms oxygen anions, forming a positively charged accumulation layer at the Co3O4 interface and a negatively charged depletion layer on In2O3, resulting in a decrease in resistance. Passing xylene (C8H 10 ) undergoes a redox reaction to release electrons, causing electrons and holes to recombine, resulting in a decrease in the accumulated positive charge in Co3O4, followed by an increase in resistance. Correspondingly, the electron concentration in In2O3 will increase, and the electrons will migrate across the potential barrier, thereby widening the potential barrier, which will also lead to an increase in resistance. This is the gas-sensitive response mechanism of Co3O4 / In2O3 heterojunction structured nanomaterials to xylene. In2O3 with a bandgap width of 6.0eV will make the heterojunction interface energy band bending more obvious, making it an ideal material for forming a heterojunction with Co3O4.
[0080] After the doping material is determined, the doping ratio also needs to be explored. Figure 1 As shown, excessive doping of In2O3 will significantly affect the crystal orientation of Co3O4 on the (3 1 1) plane. To this end, the present invention selects a variety of different doping ratios, and finally determines the optimal doping ratio of In2O3 by comparing the gas sensing properties of heterojunction structure materials with different composite ratios.
Claims
1. A xylene gas sensor based on Co3O4 and In2O3 heterojunction, characterized in that: The xylene gas sensor is mainly composed of a gas-sensitive material and an alumina ceramic tube. The gas-sensitive material is coated on the alumina ceramic tube with a coating thickness of 40 μm to 80 μm. The gas-sensitive material is composed of a cobalt tetroxide and indium trioxide heterojunction composite nanomaterial.
2. The xylene gas sensor according to claim 1, characterized in that: The alumina ceramic tube is an alumina hollow tube with a columnar body and a pure gold electrode, with a tube length of 4 mm, an outer diameter of 1.2 mm, and an inner diameter of 0.9 mm.
3. The xylene gas sensor according to claim 1, characterized in that: The cobalt tetroxide and indium trioxide heterojunction composite nanomaterial is prepared by firstly preparing cobalt tetroxide and indium trioxide materials respectively through a hydrothermal method, and then compounding them in a physical manner according to a proportion through grinding, ultrasound and magnetic stirring.
4. The xylene gas sensor according to claim 1, characterized in that: The working environment temperature of the xylene gas sensor is 240° C. to 330° C., and the material is integrated with silicon-based microelectronics.
5. A preparation process of a xylene gas sensor based on a Co3O4 and In2O3 heterojunction, characterized in that: The following steps are involved: (1) Co(NO3)2·6H2O and deionized water were added to methanol to control the Co 2+ The concentration in methanol is 0.10-0.12 mol / L, the volume ratio of methanol to deionized water is 11-27.5, and magnetic stirring is performed until the mixture is completely dissolved to obtain a mixed solution; (2) adding sodium dodecylbenzene sulfonate to the mixed solution obtained in step (1), stirring with a magnetic force until a uniform suspension is formed, controlling the concentration of SDBS to be 0.025 to 0.030 mol / L, and then performing ultrasonic treatment for 30 min to obtain a suspension; (3) transferring the suspension obtained in step (2) to a hydrothermal reaction kettle lined with polytetrafluoroethylene, performing a hydrothermal reaction at 180° C. to 200° C. for 4 h, separating the product after the hydrothermal reaction into solid and liquid using a centrifuge, washing the solid product with deionized water and anhydrous ethanol in turn for multiple times, placing the solid product in a vacuum drying oven, and drying it at 60° C. to 90° C. for more than 2 h to obtain cobalt tetroxide with a hollow nanosphere morphology; (4) In(NO3)3·xH2O was dissolved in a mixed solution of 25% NH3·H2O and ethanol, and the volume ratio of 25% NH3·H2O and ethanol was controlled to be 1:
5. 3+ The concentration of is maintained between 0.04 and 0.06 mol / L; magnetic stirring is performed for more than 3 hours to obtain a clear and transparent mixture solution; (5) transferring the mixture solution obtained in step (4) to a hydrothermal reactor lined with polytetrafluoroethylene, performing a hydrothermal reaction at a temperature of 100° C. to 120° C. for 24 hours, separating the product after the hydrothermal reaction into solid and liquid using a centrifuge, and washing the obtained solid product with deionized water and anhydrous ethanol in turn for multiple times, placing the obtained solid product in a drying oven, and drying it at 60° C. to 90° C. for 20 hours to 24 hours to obtain a precursor, and then heating the obtained precursor at 500° C. in a muffle furnace for 2 hours to obtain indium trioxide nanoparticles; (6) The cobalt tetroxide obtained in step (3) and the indium trioxide obtained in step (5) are mixed and ground into powder in proportion, and the molar ratio of Co3O4 to In2O3 is controlled between 2:1 and 999:1; the ground cobalt tetroxide and indium trioxide composite material powder is dispersed in deionized water, ultrasonically treated to form a dispersion liquid of 8 mg / mL to 10 mg / mL, and then the dispersion liquid is coated on the surface of the alumina ceramic tube, placed in a vacuum drying oven at 60°C for 15 to 30 minutes, and naturally cooled to room temperature to obtain a Co3O4 / In2O3 nanocomposite gas sensor.
6. The preparation process according to claim 5, characterized in that: In step (2), the ultrasonic power is 240W to 260W.
Citation Information
Cited By
Preparation method of Co3O4 / In2O3 heterojunction material and application of Co3O4 / In2O3 heterojunction material in electro-catalysis nitrogen reduction reaction
CN121110095A